The Approaches on Assessing the Influence of a Bus Rapid Transit System on Urban Development - Lutfi Prayogi; Yeptadian Sari (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
Bus rapid transit (BRT) has been recognized compatible to be built in conjunction with transit-oriented development (TOD). However, little has been explained on how a BRT system may support TOD, including how a BRT system may influence urban development. This article explores the utilized approaches to assessing the influence of a BRT system on urban development under the TOD framework. It explores the justification, methodology, and typical findings of each approach. This article was written through literature review processes that are reviewing the TOD goals and principles and reviewing the utilized approaches. It was found out that there are currently two partially appropriate utilized approaches on assessing the influence of a BRT system on urban development under the TOD framework, that are evaluating the premium brought to properties around the system and assessing the transit ridership change around the system. It was concluded that the two utilized approaches need to be developed, and other new approaches need to be invented.